A política científica e tecnológica e a questão da democratização da ciência: uma análise a partir da extensão universitária brasileira com protagonismo feminino - Ardigó, Rafaela Mota (2024)
Although comparative studies in the light of international experiences are important for thinking about processes of democratization of science, changing the reality that surrounds Brazilians requires a commitment to developing internal research to support public policies that are endogenous and coherent with our historical times. In this sense, this thesis is theoretically justified on the premise that the structural analysis of capitalism from the lens of sex and race is a gap in the literature of Latin American critical thinking in CTS. From a practical perspective, this study is justified by the perception that with the advance of the inclusion of women researchers and scientists in university chairs, even though it is a marginal agenda, research objects that were once relegated to the private space are beginning to take on a political body, shifting the scientific cadence and forcing a process of oxygenation of PCTI policies and politics in Brazil. Based on these gaps, the main objective of this work was to explore the contributions of extension practices with female protagonists in proposals for the democratization of science in the Brazilian context. As a secondary objective, I proposed to demonstrate how both, the contributions and the controversies identified, can oxygenate national PCTI by adding social and regional issues to shape a public policy that is more suited to the type of development needed in a peripheral reality than the ones present in the countries where mainstream PCTI is generated and disseminated globally. To this end, I used a multi-method methodology guided by intersectionality as methodology. Qualitatively, it consists of databases from ethnographic processes developed in three case studies involving women extension scientists. Quantitatively, I developed surveys data collected in secondary-bases available in public platforms on the internet related to the subject of this thesis. As a result of the analyses, I suggest the systematization of two parallel guidelines that can contribute to endogenous processes for the democratization of science in Brazil. The first, influenced by Latin American critical thinking, suggests changes to be implemented in PCTI politics based on a social learning system approach that favors the analysis and political training of scientists in conjunction with society based on three axes of action: social reproduction, representativeness in spaces of power and action in territories. The second, influenced by the hegemonic model of mission-oriented innovation, uses an approach based on the Sustainable Development Goals (SDGs), suggesting four lines of action in PCTI policies: public-private partnerships for job creation, scientific and technological education, valuing careers in university extension and teaching practices for inclusion in STEM from a popular perspective. Although controversies are a challenge for the integration of the scientific community, even when the differences are only epistemological in a social group with commonalities, the results indicate that the paths that lead to the processes of democratization of science in Brazil will not occur without the commitment to present proposals that help to reduce the persistent asymmetries of power associated with gender, race, and class in Brazilian society.